We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
172
2
avatar+38 

The equation of the circle that passes through (-1,6) and which has a center at (2,3) can be written as x^2 + y^2 + Ax + By + C = 0. Find A*B*C

 

 

Please help thanks!!!

 Mar 6, 2019
 #1
avatar+6042 
+2

\(r^2 = (-1 - 2)^2 + (6-3)^2 = 18\\ (x-2)^2 + (y-3)^2 = 18\\ x^2 - 4x + 4 + y^2 - 6y + 9 = 18\\ x^2 + y^2 -4x -6y-5 = 0\\ (-4)(-6)(-5) = -120\)

.
 Mar 6, 2019
 #2
avatar+23145 
+3

The equation of the circle that passes through (-1,6) and which has a center at (2,3)
can be written as x^2 + y^2 + Ax + By + C = 0.
Find A*B*C

 

\(\text{Let $x_c=2,\ y_c =3,\ x_p=-1,\ y_p=6$} \)

 

\(\begin{array}{|rcll|} \hline (x-x_c)^2+(y-y_c)^2 &=& r^2 \quad | \quad r^2 = (x_p-x_c)^2+(y_p-y_c)^2 \\ (x-x_c)^2+(y-y_c)^2 &=& (x_p-x_c)^2+(y_p-y_c)^2 \\ x^2-2xx_c+ \not{x_c^2}+y^2-2yy_c+\not{y_c^2} &=& x_p^2-2x_px_c+\not{x_c^2}+y_p^2-2y_py_c+\not{y_c^2} \\ x^2-2xx_c +y^2-2yy_c &=& x_p^2-2x_px_c +y_p^2-2y_py_c \\ x^2+y^2+(-2x_c)x+(-2y_c)y &=& x_p^2-2x_px_c +y_p^2-2y_py_c \\ x^2+y^2+ (-2x_c) x+ (-2y_c)y -(x_p^2-2x_px_c +y_p^2-2y_py_c ) &=& 0 \\ x^2+y^2+\underbrace{(-2x_c)}_{=A}x+\underbrace{(-2y_c)}_{=B}y +\underbrace{(2x_px_c+2y_py_c -x_p^2-y_p^2)}_{=C} &=& 0 \\\\ A&=& -2x_c\\ &=& -2\cdot 2 \\ \mathbf{A} &=& \mathbf{-4} \\\\ B&=& -2y_c\\ &=& -2\cdot 3 \\ \mathbf{B} &=& \mathbf{-6} \\\\ C &=& 2x_px_c+2y_py_c -x_p^2-y_p^2 \\ &=& 2(-1)2+2\cdot 6 \cdot 3-(-1)^2-(6)^2 \\ &=& -4+36-1-36 \\ \mathbf{C} &=& \mathbf{-5} \\\\ A\cdot B\ \cdot C &=& (-4)(-6)(-5) \\ &=& -4\cdot 5 \cdot 6 \\ \mathbf{A\cdot B \cdot C } &=& \mathbf{-120} \\ \hline \end{array} \)

 

 

laugh

 Mar 6, 2019

8 Online Users

avatar